Does environmental information disclosure promote sulfur dioxide (SO2) remove？New evidence from 113 cities in China. (25th May 2021) - Zhong, Shen; Li, Jian; Zhao, Ruili
Abstract: Sulfur dioxide (SO2 ) emission reduction is one of the main goals of China environmental sustainable development. Environmental information disclosure, as a means of environmental regulation, have significant effect on SO2 removal rate. This paper uses the Pollution Information Transparency Index (PITI) of 113 cities in China from 2008 to 2017, jointly released by Institute of Public and Environmental Affairs and Natural Resources Defense Council, to empirically analyze the impact of pollution information transparency index on SO2 removal rate and its spatial spillover effect by employing fixed effect model and spatial Durbin model. Theoretically, environmental information disclosure will exhibit a positive effect on SO2 removal of the local city through the "target accountability" and "backward forcing effect", and displays a spatial spillover effect on the surrounding cities through the "warning effect" and "learning effect". The empirical results prove the theoretical analysis: (1) SO2 removal amount and emissions have a significant positive spatial correlation, show spatial agglomeration characteristics of "high-high" or "low-low"; (2) In the local city, pollution information transparency index shows a significant emission reduction effect, that is, it reduces the SO2 emission and improves SO2 removal rate; (3) There is a significant positive spatial spillover effect on the environmental information disclosure. A 1% increase in pollution information transparency index of surrounding cities will contribute to the increase of SO2 removal rate of the local city by about 0.959%, which verifies the "warning effect" and "learning effect"; (4) Further analysis verdicts that environmental information disclosure also has emission reduction effect on other industrial pollutants, and instrumental variable model and robustness test support the above conclusions. This paper provides theoretical and empirical support for the construction of environmental information disclosure system. Highlights: Information disclouse shows obvious positive effect on SO2 removal rate among cities. Neighboring cities show similar characteristics in industrial pollution. PITI can reduce the emission of major industrial pollutants. The study provides a reference for role of information disclosure in sustainability.